Caregiver Burden of People with Schizophrenia: a concept analysis - Gunawan, Indra; Huang, Xuan-Yi; Restiana, Nia; Rosnawanty, Rossy; Saryomo, Saryomo; Falah, Miftahul (South East Asia Nursing Research, 2023)
The term burden of care has been widely used in current nursing reference sources, but the definition of the concept of the burden of caring for caregivers of people with Schizophrenia has never been studied. Therefore, this article aims to analyze and provide relevant information related to the caregiver burden of people with Schizophrenia. This literature study uses an electronic article search tool from several online database sources such as (CINAHL (Cumulative Index for Nursing and Allied Health), PubMed, Google Scholar, Cochrane Library), health official websites (both non-government or government), and dictionaries. This analytical study adopts the principles of Walker and Avant to identify the attributes, antecedents, and consequents of this concept. This study has identified the attributes, antecedents, and consequences of the concept of caregiver burden of people with Schizophrenia. The attributes include Unequal distribution of responsibilities, persistent fatigue, and perception. Meanwhile, the antecedents are a lack of formal and informal social support, the conflict of various duties, and limited social activities. The last, in this study, has revealed the concept's negative consequences, including decreased quality of care, poor quality of life, and physical and psychological problems. A clear understanding of the caregiver burden of people with Schizophrenia has been defined. The results of this study can be used as a knowledge base for scientific development to improve the quality of nursing interventions, especially for caregivers of people with Schizophrenia.